Length and Roughness Perception in a Moving-Plateau Touch Display. (5th April 2012) - Watanabe, Junji; Godai, Yusuke; Ando, Hideyuki
Abstract : We have proposed a tactile geometry display technique based on active finger movement. The technique uses a perceptual feature that, during finger movement, the length of a touched object is perceived to increase when the object is moved in the same direction as the finger movement or to decrease when it is moved in the opposite direction. With this display technique, a wide range of tactile shapes can be presented with realistic rigid edges and continuous surfaces. In this work, to further develop our technique, we performed psychophysical experiments to study perceptions of length and roughness under this presentation technique. The results indicated that the elongation (shrinkage) of the object can be observed regardless of the roughness of the touched object and that the perceived roughness of the object slightly changes but the changes are much smaller than those theoretically expected.